A systematic literature review on AAOIFI standards. Issue 2 (4th February 2021) - El-Halaby, Sherif; Aboul-Dahab, Sameh; Bin Qoud, Nuha
Abstract : Purpose: This paper aims to systematically review the existing studies for Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) standards which include different tracks of researches and then identify the gaps to propose opportunities for future research. Design/methodology/approach: By adopting a systematic literature review approach, 46 papers that were published between 2000 and 2020 from 23 journals concerned with AAOIFI were selected for review and analysis. Findings: The authors combine electronic searches to identify relevant studies using keywords such as "AAOIFI" or and "Islamic standards." In light of the existing studies' limitations, this paper derives and summarizes five leading future research tracks: identifies the research gaps in AAOIFI and then suggests that AAOIFI still requires more empirical analyses; identifies the alternative analytical methods as meta-analysis; identifies additional measurements for macro and microeconomics factors; identifies recent tracks as corresponding to Covid-19 pandemic; and future studies should consider the role of central banks and positive criticism for AAOIFI. Practical implications: This analysis address the literature gaps on measuring compliance, determinants and consequences of AAOIFI adoption as this study serves as a guide for the researchers, regulators and Islamic financial institutions in research associated with this area. The findings would support AAOIFI, regulators and related authorities across jurisdictions with suggestions on improving the current AAOIFI practices. Originality/value: This literature review is a historical record and guidance for researchers who seek to examine and explore several questions about AAOIFI. To the best of the authors' knowledge, this is the first paper that applies systematic literature review over AAOIFI research field.